Pasture intake and milk production of dairy cows grazing annual ryegrass with or without corn silage supplementation - Miguel M.F.* (2014)
The use of corn silage to supplement grazing dairy cows can improve milk production and nutrient intake when the substitution rate is low. This enhancement occurs by increasing the total DM intake. The hypothesis tested in this study was that increasing corn silage supplementation level of dairy cows grazing annual ryegrass at medium pasture allowance could increase substitution rate and decrease milk production response. Three supplementation levels (0, 4 and 8 kg DM/day) were compared for dairy cows strip-grazing annual ryegrass (Lolium multiflorum cv. Common). The study was arranged as a 3 × 3 Latin square design, repeated three times using nine Holstein lactating cows. The supplement was a 7:1 mixture based on the DM of corn silage and soybean meal and was offered individually twice daily after the morning and afternoon milkings. Each treatment group of cows grazed separately at a common daily pasture allowance of 35 kg DM/cow to ground level. Each experimental period was 12 days, with an 8-day adaptation and a 4-day measurement period. The individual pasture intake was measured from Day 9 to Day 12 using the n-alkane technique. The daily pattern of grazing and ruminating times were measured by visual observations. The supplement DM intake was lower than expected, averaging 3.0 and 4.3 kg DM/day for cows receiving 4 and 8 kg DM/day, respectively. Pasture and supplement energy value were 7.0 and 6.3 MJ of NEL/kg DM, respectively. The substitution rate averaged 0.2 and was unaffected by the supplementation level. The pasture intake was similar for all treatments (14.0 kg of DM/day), and total DM intake and milk production (+0.5 kg of milk/kg DM of supplement) increased linearly with increasing supplementation level. The daily grazing time was shorter by 111 min/day for the supplemented cows than for the unsupplemented cows. Cows grazing the annual ryegrass at medium pasture allowance improved their total DM intake and individual performance when supplemented with corn silage. © CSIRO 2014.